Genomics of perivascular space burden unravels early mechanisms of cerebral small vessel disease. (20th December 2022) - Duperron, Marie‐Gabrielle; Knol, Maria J.; Grand, Quentin Le; Evans, Tavia E; Mishra, Aniket; Roshchupkin, Gennady V.; Konuma, Takahiro; Tregouët, David Alexandre; Romero, Jose Rafael; Frenzel, Stefan; Luciano, Michelle; Hofer, Edith; et al.
Abstract: Background: Perivascular space (PVS) burden is an emerging MRI‐marker of cerebral small vessel disease (cSVD), a leading cause of stroke and dementia. Underlying mechanisms of PVS are unknown. PVS are thought to be related to the glymphatic system, involved in brain clearance of molecules such as amyloid beta. We aimed to decipher the genetic underpinnings of PVS burden. Method: We conducted genome‐wide and whole‐exome association studies in N = 39, 823 participants for white matter (WM) PVS, N = 40, 000 for basal ganglia (BG) PVS and N = 40, 095 for hippocampal (HIP) PVS (21 population‐based cohorts, 66.3±8.6 years). As PVS were rated with different scales across cohorts, we tested association of genetic variants with the top quartile of PVS burden distribution in each cohort followed by a sample‐size weighted meta‐analysis. We searched for shared genetic variation with related vascular and neurological phenotypes using linkage disequilibrium‐score regression, explored causality of associations with putative risk factors using Mendelian randomization and conducted extensive functional exploration of identified PVS loci using multiple bioinformatics approaches, including transcriptome‐wide association studies. Result: We identified 24 genome‐wide significant PVS risk loci. These showed association with WM PVS already at age 20 in 1, 748 young healthy adults, suggesting an important role of early‐life factors. PVS loci were enriched in genes causing early‐onset leukodystrophies and genes expressed in fetal brain endothelial cells. Mendelian randomization analyses supported causal associations of high blood pressure with BG and HIP PVS, and of BG PVS with stroke. Transcriptome‐wide association and colocalization analyses suggest causal implication of 11 genes, that could be prioritized for experimental follow‐up. Two‐thirds of PVS loci point to novel pathways, involving extracellular matrix, membrane transport, and developmental processes, with enrichment in targets of existing drugs for vascular cognitive, and infectious disorders. Conclusion: In this first gene‐mapping study of PVS, one of the earliest MRI‐markers of cSVD, we describe 24 genome‐wide significant risk loci. Our findings provide completely novel insight into the biology of PVS across the adult lifespan and its contribution to cSVD pathophysiology, with potential for genetically informed prioritization of drug targets for prevention trials of cSVD, a major cause of stroke and dementia worldwide.